Inteleukin-6 secretion during pathophysiological events of pregnancy – preterm birth, preeclampsia, fetal growth restriction, gestational diabetes mellitus (Journal of Medical Science, 2024)
Cytokines play a role in nearly all reproductive and pregnancy processes. These proteins are expressed in various body fluids and tissues related to reproduction. Interleukin-6 (IL-6) stands out as one of the best-characterized members of the cytokine family. This protein has an immense and imperfectly understood impact on both normal and pathological aspects of human pregnancy. IL-6 exerts a wide range of effects on the immune system, and it plays crucial roles in regulating inflammation processes and homeostasis. Herein, we summarize current knowledge on IL-6 secretion during pathophysiological events of pregnancy: preterm birth, preeclampsia, fetal growth restriction and gestational diabetes mellitus. Cytokines, particularly interleukin-6, play crucial roles in regulating pregnancy physiology. Maintaining IL-6 homeostasis is essential for the health of both the mother and fetus. IL-6 supports pregnancy by influencing uterine receptivity, trophoblast function, and immune interactions at the feto–maternal interface. Disrupted IL-6 expression may contribute to various pregnancy complications. A deeper understanding of IL-6 regulation can help detect dysregulation and potentially optimizing pregnancy outcomes. Addressing knowledge gaps identified in this review is vital for improving current practices and enhancing pregnancy outcomes.